Analisis Kepuasan Kerja Karyawan Fore Coffee Bintaro Xchange Menggunakan Pendekatan Importance Performance Analysis (IPA) - achmad fikri ramadhan; Nanang Alamsyah; Wendy Febrianty (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2026)
This study aims to analyze employee job performance at Fore Coffee Bintaro Xchange by identifying the gap between the level of importance and the level of satisfaction perceived by employees. Using a quantitative descriptive approach, data were collected through a structured Likert-scale questionnaire distributed to all 12 employees using total sampling. The Importance Performance Analysis (IPA) method was employed to measure and map the performance of ten job performance indicators (A1–A10) based on their importance and satisfaction values. The results show that the overall level of satisfaction (mean = 4.29) slightly exceeds the level of importance (mean = 4.24), indicating that job performance generally meets employee expectations. However, the GAP analysis reveals several indicators with negative values, particularly Judgment (A6), Initiative & Resourcefulness (A7), and Leadership Qualities (A8). These three indicators fall into Quadrant I (Concentrate Here), signifying high importance but low satisfaction, and therefore require immediate managerial attention. Indicators such as Knowledge of Job (A2), Adaptability (A4), and Dependability (A5) are positioned in Quadrant II (Keep Up the Good Work), demonstrating strong performance that should be maintained. Meanwhile, Productivity (A3) and Performance (A10) are categorized in Quadrant III (Low Priority), while Quality of Work (A1) and Interpersonal Relations (A9) fall into Quadrant IV (Possible Overkill). Overall, the findings highlight the need for managerial improvement in decision-making, initiative, creativity, and leadership capabilities to enhance employee performance and organizational effectiveness